Cellular proteins associated with simian virus 40 early gene products in newly infected cells. - Yang, Y C (1979)
Immunoprecipitates of extracts of simian virus 40-infected permissive monkey kidney cells contained two proteins with molecular weights of 56,000 and 32,000 (52K and 32K) in addition to the known viral early gene products. Immunoprecipitates of cells infected with the 0.54-0.59 deletion mutants that lack the viral 17K gene product did not contain thhe 56K and 32K proteins. The additional proteins appeared in immunoprecipitates of deletion mutant extracts if unlabeled extracts of wild-type-infected cells were added before addition of antiserum. The proteins can also be identified in uninfected cells by co-precipitation with unlabeled viral proteins. Thus, it appears that the 56K and 32K proteins are cellular products that associate with the viral proteins, the 17K in particular, and are indirectly immunoprecipitated by anti-tumor serum.